Penerapan Metode Workshop dan Penelitian Dalam Meningkatkan Kemampuan Komunikasi Pemasaran Produk Olahan Singkong Alen-Alen di Desa Perlanaan - Fajar, Khairul; Ritonga, Elfi Yanti (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
Perlanaan Village is a potential village with abundant natural resources. One of the leading commodities in the village is cassava. Most of the MSMEs in Perlanaan Village produce alen-alen because they have promising business prospects. However, in practice, MSMEs have not been able to create good marketing conditions. MSMEs' limited knowledge in utilizing social networks is an inhibiting factor in the development of alen-alen businesses. This research was conducted in November - December 2023 in Perlanaan Village. This research aims to analyze marketing communication strategies in increasing sales of processed alen-alen cassava products in Perlanaan Village. The research method used is a case study. Data collection methods are carried out through interviews, observation and documentation. The data used in this research are primary data and secondary data. The sampling technique uses non-probability using purposive sampling. The respondents used consisted of a group of PKK women and 5 MSMEs. The data analysis method used is a qualitative descriptive analysis method. The research results show that the use of social media is a marketing communication strategy that is quite effective in attracting consumer attraction. Marketing communication is also very important in the marketing strategy for processed Alen-Alen cassava products. Community empowerment activities have the potential to increase the community's knowledge and interest in learning in utilizing the abundance of cassava into more innovative food snack products as well as the rise of social media which has become a strategic tool in marketing communications.